Comparative Analysis of Volatile Components from Rough and Manufactured Roots of Radix Gentianae macrophyllae by GC-MS. Issue 5 (3rd September 2018) - Song, Jiuhua; He, Yunqing; Chen, Fengzheng; Tang, Qiong; Cheng, Ying; Liu, Sujun
Abstract: Radix Gentianae macrophyllae is a traditional Chinese medicine (Qinjiao in Chinese). In this paper, the volatile components extracted from rough Qinjiao (raw, unprocessed Qinjiao)and manufactured Qinjiao (Yinpian, commercial Qinjiao) roots were investigated and comprehensively analyzed and compared by gas chromatography-mass spectrometry (GC-MS) and related chemometrics methods for the first time. The main components were identified belonging to aldehydes, aromatics, fatty acid derivatives, alcohols, esters, ketones, alkanes, terpenoids and others. The discrimination of the samples from manufactured Qinjiao (Yinpian) and rough Qinjiao was achieved by principal component analysis (PCA). The results confirmed that rough samples were characterized by the presence of trans -2-nonenal, linalool and nonanol while manufactured samples were characterized by the presence of pentadecanoic acid and stearyl acetate. The results proved that GC-MS fingerprint combined with PCA approach is a simple, rapid and novelty method which is suitable for the quality control of the raw materials of Qinjiao.